ENGLISH PHONOLOGY FOR LANGUAGE LEARNERS: EXPLORING LEARNERS’ PREFERENCES - Ika Adhitiyan Utami; Alies Poetri Lintangsari (Sanata Dharma University, 2021)
English Phonology is an absolutely necessary subject that should be mastered by foreign language learners in learning English. It is taught mostly at university level. However, there are still many students who are not aware of how important learning English Phonology is and less interested in learning this subject. There also has been little study that concerns students' preferences in learning English Phonology whereas knowing students’ preferences on topics or themes used in learning materials is a good step to make better learning outcomes. This study aims to investigate the most and least preferred topics and themes by EFL (English as a Foreign Language) students during English Phonology learning. This was a descriptive quantitative research by using a cross-sectional survey design. The data was collected with questionnaire from 112 participants of English Education Study Program students. The result showed phonological process pattern in English becoming the most preferred topic and theme while segmental phonology becoming the least preferred topic and theme in learning English Phonology.